2021
DOI: 10.3389/fimmu.2020.617089
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Human Monoclonal Antibodies to SARS-CoV-2 Proteins With Tissue Antigens: Implications for Autoimmune Diseases

Abstract: We sought to determine whether immune reactivity occurs between anti-SARS-CoV-2 protein antibodies and human tissue antigens, and whether molecular mimicry between COVID-19 viral proteins and human tissues could be the cause. We applied both human monoclonal anti-SARS-Cov-2 antibodies (spike protein, nucleoprotein) and rabbit polyclonal anti-SARS-Cov-2 antibodies (envelope protein, membrane protein) to 55 different tissue antigens. We found that SARS-CoV-2 antibodies had reactions with 28 out of 55 tissue anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
253
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(303 citation statements)
references
References 63 publications
4
253
0
2
Order By: Relevance
“…Thus, it is obvious that there is a link between the pathogenesis of COVID-19 and autoimmune thyroid disease. In one study, SARS-CoV-2 monoclonal antibodies were applied to different tissues and the thyroid gland was reactive, which has proved that COVID-19 might lead to thyroiditis [ 23 ]. However, clinical studies showed contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is obvious that there is a link between the pathogenesis of COVID-19 and autoimmune thyroid disease. In one study, SARS-CoV-2 monoclonal antibodies were applied to different tissues and the thyroid gland was reactive, which has proved that COVID-19 might lead to thyroiditis [ 23 ]. However, clinical studies showed contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COVID-19 infection should routinely be screened for major psychiatric symptoms; they should be prospectively followed because many of these patients will develop a post-COVID syndrome and chronic fatigue, and depression, which are cognitive impairments that are major features of this syndrome. The neuro-immune approach is warranted because: (a) the psychiatric symptoms during infection are associated with inflammation, immune disorders, and oxidative stress, and (b) increased autoimmunity is one of the features of COVID-19 infection [ 56 ], which is probably associated with the post-COVID-19 syndrome.…”
Section: Effects Of the Covid-19 Pandemic On Public Mental Health In Thailandmentioning
confidence: 99%
“…Recently, novel human antibodies raised against SARS-CoV-2 spike protein S1 and S2 domains or against SARS-CoV-2 nucleoprotein were obtained and generated as fully human IgG1 antibodies 28 30 . Cross-reactive patterns between SARS-CoV-2 proteins and autoimmune target proteins were found to play a role in the systemic inflammatory response in patients affected by Covid-19 leading to the development of autoimmune diseases post-infection in susceptible subgroups of patients 31 .…”
Section: Discussionmentioning
confidence: 99%